ANALISIS PEMBIAYAAN PERBANKAN (STUDI KASUS) PADA BANK SYARIAH PT. BANK MUAMALAT INDONESIA - Nur Nadila Harisanti; Micha Ella Br Meliala; Renny Oktafia (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
In Indonesia, Islamic banking has made rapid progress since the enactment of Banking Law No. 10 of 1998. Funding risk management is an important aspect of Islamic banking operations. Therefore, efficient financing management is necessary to maintain financial stability. An increase in the volume of financing by Islamic banks can contribute to the profitability of these financial institutions. The case study of Bank Muamalat Indonesia shows the bank's commitment to comply Sharia principles, especially in terms of lending to businesses and individuals. The purpose of this study is to conduct an analysis of funding conducted by PT. Bank Muamalat Indonesia as a case study in the context of Islamic banking. The focus of the analysis is on raising funds and disbursing loans carried out by Bank Muamalat. It is expected that the results of this research can have an impact on improving Bank Muamalat Indonesia's financial management.